Understanding the Socialist-Market Economy in Vietnam - Ngoc Anh Nguyen (Ital Publication, 2022)
The economic reform started in 1986 has transformed Vietnam from one of the world’s poorest countries 35 years ago to a lower middle-income country (MIC) in 2010. Poverty rates dropped from 70% in 1986 to below 2% in 2021. The transition from a central planning system to a socialist market economy is the fundamental underlying factor of Vietnam's success. Using the historical institutional framework that Lee (2018) [1] developed, this study aims to explore the country’s transition from a central planning system to a socialist market economy over the past three decades. The findings demonstrate that the country’s transition to a socialist market economy has been taking a gradualism and dualism path like China. In addition, the study also illustrates how the economic reform and globalization processes pushed the institutional transformation in Vietnam to meet the demands of multiple economic sectors and ownerships as well as accommodate international commitments that the country entered. Finally, Vietnam has been cautious in its political reform over the past few decades. Yet, this is inevitable as a result of the country’s socio-economic development process as well as the global and regional rapid changing context. The implications for Vietnam include: (i) Vietnam needs to transform its growth model toward a knowledge-based, higher-added-value, and more environmentally-friendly pattern; (ii) while there is significant progress in institutional transformation, bottlenecks and challenges remain. This should be addressed effectively to unlock the country’s potential; (iii) political system reform is inevitable as conditions are mature. Domestic demands and international requirements are putting increasing pressure on the changes. However, this process will likely move forward and take place within the political system rather than by civil society or outsiders. Doi: 10.28991/ESJ-2022-06-05-03 Full Text: PDF